Mediation Role of Perceived Organizational Support on Nurses’ Work Engagement and Leadership Styles - Aida Mehrad; Jordi Fernández-Castro; Maria Pau González Gómez de Olmedo; Rosa García-Sierra (Nurse Media: Journal of Nursing, 2022)
Background: Nurses’ work engagement is essential both for the quality of the service provided and occupational health. However, there is a lack of adequate information about nurses’ engagement in healthcare organizations that are affected by various factors in the context of Health Psychology.